A Temporospatial Study of Sympathetic Skin Response and Electroencephalogram in Oral Mucosa Thermal Perception - Zhang, Hao; Hu, Shengjing; Wang, Zhangang; Li, Xiang; Wang, Suogang; Chen, Gang (Frontiers in Neuroscience, 2022)
Objective To investigate the temporospatial changes in sympathetic skin response (SSR) and electroencephalogram (EEG) under thermal stimuli and to draw a topographic map of SSR threshold temperature of the oral mucosa. Materials and Methods A total of 40 healthy volunteers (24 men, 16 women, mean age of 23 ± 3) were enrolled. Thermal stimuli were applied to the 35 partitions of oral mucosa starting from 36°C at the gradience of 1°C and the lowest temperature evoked SSR was defined as SSR threshold temperature. SSR and EEG signals at 45, 48, 51, and 54°C were then recorded synchronously. Results The SSR threshold temperature increased from the anterior areas to the posterior areas. No significant difference between bilateral corresponding areas or between genders was observed. The SSR amplitude value increased from 45 to 54°C in the same area, while the highest value was recorded on the tip of the tongue and decreased backwardly from the anterior area. There were significant differences in latency of SSR between the tip of the tongue and the molar areas of the oral cavity (p < 0.05). Reduction in the alpha frequency band was observed after thermal stimuli, and there were statistical differences between baseline and thermal stimuli in all four degrees of temperatures (p < 0.05). Conclusion The result of the experiment revealed that the autonomic and central nervous system (CNS) played important roles in thermal perception of oral mucosa and could be helpful for better understanding of pathological mechanism of burning mouth syndrome (BMS).